An analysis method for a non-wrapped mineral inlay state

CN122410003BActive Publication Date: 2026-09-22CHANGCHUN GOLD RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610875233.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-09-22
Estimated Expiration
2046-06-17

AI Technical Summary

Technical Problem

[0003]当前工艺矿物学分析方法存在以下的不足:首先,现有方法以定性或半定量为主,显微镜或扫描电镜分析多停留在“可见粒间”、“可见裂隙”等层面描述,缺乏对连晶比例、接触长度等级、粒间与非粒间占比的系统定量表征,不同连晶比例多对应解离行为的显著差异,但现有方法无法给出按接触长度占比分级的定量结果;其次,现有方法多忽略接触形态差异,现有自动矿物学(如MLA、QEMSCAN、TIMA等)能获取矿物组成与颗粒面积,但难以区分“粒间接触”与“无裂隙包裹接触”,也无法量化描述“目的矿物在多个矿物颗粒间的嵌存程度”;第三,包裹态与非包裹态混同处理严重,多数方法未将易解离的非包裹状态与难解离的包裹状态区分计算,导致解离度预测误差大,误导磨矿与浮选工艺设计

Benefits of technology

1、本发明提供的方法系统性地量化了目的矿物的嵌布状态,通过区分“粒间接触”(含裂隙)与“包裹接触”(无裂隙),并引入粒间修正系数 c,能够更准确地判断目的矿物是处于矿物颗粒边界还是被完全包裹,为后续选矿工艺(如磨矿解离)提供关键依据。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122410003B_ABST
    Figure CN122410003B_ABST
Patent Text Reader

Abstract

The application discloses a kind of non-encapsulated state mineral inclusion state analysis method, belong to geological test analysis and process mineralogy technical field.Its steps include: preparation multi-faceted block sample and glue injection treatment;Under microscope, distinguish the mineral contact containing fissure and not containing fissure, calculate intergranular correction coefficient;By automatic mineralogy analysis, obtain the purpose mineral particle area weight;The centroid distance and contact length of mineral particle are measured, and effective area weight is calculated;Finally, construct multiple inclusion state characteristic parameters, quantify the intergranular contact state of purpose mineral, pore contact state and the proportion of intercrystalline, and contact range grade.The present application can systematically distinguish non-encapsulated state and encapsulated state mineral, fine characterization intercrystalline proportion and contact strength, significantly improve the accuracy of dissociation behavior prediction, provide reliable, comparable quantitative basis for beneficiation process design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of geological testing and analysis and process mineralogy, specifically to an analytical method for the non-enclosed mineral embedding state. Background Technology

[0002] In mineral processing and technological mineralogy research, the embedding state of the target mineral is one of the key factors determining its liberation behavior and beneficiation recovery rate. Traditional studies have focused on inclusion minerals, i.e., target minerals completely surrounded by a single type of other minerals without fracture development. Because such inclusion minerals, especially fine-grained ones, are difficult to liberate under conventional grinding conditions, fine grinding or special processing methods are usually required, resulting in high energy consumption and low recovery rates. However, non-inclusion minerals are more commonly found in actual ores, including: target minerals distributed between grains (located between one or more minerals (with clear contact boundaries) and in direct contact with each mineral), target minerals developed along pores, and target minerals existing in different proportions of intergrowth. It is well known that target minerals in these non-inclusion states have significantly better liberation properties than inclusion minerals and possess higher beneficiation potential. Therefore, quantitatively studying the proportion of different non-inclusion embedding states (especially different intergrowth ratios) is of significant engineering importance for optimizing grinding fineness, predicting separation behavior, and designing rational beneficiation processes.

[0003] Current process mineralogical analysis methods have the following shortcomings: First, existing methods are mainly qualitative or semi-quantitative. Microscopic or scanning electron microscopy analyses often only describe "visible intergranular areas" and "visible cracks," lacking a systematic quantitative characterization of the intergranular ratio, contact length grade, and the proportion of intergranular and non-intergranular areas. Different intergranular ratios often correspond to significant differences in liberation behavior, but existing methods cannot provide quantitative results based on the proportion of contact length. Second, existing methods often ignore differences in contact morphology. Existing automated mineralogical methods (such as MLA, QEMSCAN, TIMA, etc.) can obtain mineral composition and particle area, but they have difficulty distinguishing between "intergranular contact" and "crack-free encapsulated contact," and cannot quantify the "degree of embedding of the target mineral among multiple mineral particles." Third, the treatment of encapsulated and non-encapsulated states is seriously mixed. Most methods do not distinguish between easily liberated non-encapsulated states and difficult-to-liberate encapsulated states in calculations, resulting in large errors in the degree of liberation prediction, which misleads the design of grinding and flotation processes.

[0004] In view of this, it is necessary to study an analytical method for the non-encapsulated mineral embedding state, which can distinguish between intergranular, pore and different crystallization ratios, accurately characterize the true contact relationship of the target mineral, and provide a scientific basis for efficient mineral processing technology. Summary of the Invention

[0005] In view of the technical problems existing in the background art, the present invention provides an analytical method for the non-encapsulated mineral embedding state, which is used to quantitatively characterize the intergranular contact, porosity distribution, and crystallization ratio of the target mineral in the ore, providing a basis for mineral processing design. This method distinguishes and quantifies the contact relationship between the target mineral and surrounding minerals, especially the difference between intergranular contact and encapsulated contact. By introducing characteristic parameters such as intergranular correction coefficient, centroid distance, contact edge length, and effective area weight, combined with multi-faceted sample analysis and automated mineralogical technology, the method systematically characterizes the embedding state of the target mineral in different types of minerals (such as metal sulfides, minerals containing the target element, and other minerals) and pores. Finally, multiple quantitative characteristic parameters are constructed to achieve a fine classification of crystallization ratio, contact range level, and encapsulation degree, solving the problem that traditional methods can only qualitatively describe and are difficult to quantify crystallization ratio and contact morphology.

[0006] This invention provides a method for analyzing the embedding state of non-encapsulated minerals, comprising the following steps: S1, Sample processing: Prepare three-dimensional multi-faceted samples to obtain at least three adjacent test surfaces that share a vertex; S2, Intergranular contact identification: Perform optical analysis on the surface to be tested to obtain the contact type parameters of the target mineral in the ore. The contact type parameters include an intergranular correction coefficient used to characterize the proportion of the target mineral in the intergranular contact state. S3, Particle Information Acquisition: Perform automatic mineralogical analysis on the surface to be measured to obtain the area parameters of the target mineral particles; S4, Contact geometry measurement: Measure the geometric contact parameters of the target mineral particles, the geometric contact parameters including: the centroid distance dn.m of the target mineral particles, and the contact side length Ln.m of the target mineral particles, where m is at least one non-target mineral category or pore size, and n is the number of the target mineral particles. S5, Calculation of contact characteristic parameters: Calculate the contact characteristic parameters of each contact type based on the contact side length and the centroid distance; the contact characteristic parameters include the effective area of ​​the contact region between the nth target mineral particle and the mth type of non-target mineral, and the weight of the effective area relative to the total effective area of ​​all contact regions of the target mineral particle; S6, Quantitative analysis of embedding state: Based on contact characteristic parameters and combined with the intergranular correction coefficient and area parameters, calculate the embedding state characteristic parameters of the target mineral to quantitatively characterize the intergranular contact, porosity distribution and crystallization ratio of the target mineral.

[0007] As a further improvement of the present invention, in step S6, the embedding state characteristic parameters include H1~H8 classified according to the type of contact mineral and the contact range interval. H1~H4 are classified according to the effective area weight of the contact range interval to characterize the embedding distribution rate of different mineral combinations and cracks / pores. H5~H7 characterize the embedding distribution rate of the target mineral edge being a single mineral and located between grains. H8 characterizes the encapsulation state distribution rate of the target mineral edge being the same type of mineral. The distribution rate of the target mineral's embedding state is calculated using the following formula: Hp.q = (1 / 3) × ΣWn.e / f, where p is 1~4, q is the effective area weight, Q is the contact range, Wn.e is the relative percentage of the target mineral particles, n is the number of the target mineral particles, f is the number of sample blocks, and e is the face number of the sample measurement surface; or Hp = (1 / 3) × ΣWn.e / f, where p is 5~7; or H8 = (1-c) × (H5+H6+H7) / c; The contact range interval Q is divided into the following categories according to the proportion of effective area weight q: greater than 0% and less than or equal to 25% (zone 1), greater than 25% and less than or equal to 50% (zone 2), greater than 50% and less than or equal to 75% (zone 3), and greater than 75% and less than or equal to 100% (zone 4).

[0008] As a further improvement of the present invention, the distribution rate of the embedded state includes the following parameters: H1 is the distribution rate when the edge of the target mineral simultaneously contains fissures, metal sulfides, and at least one other mineral containing the target element and another other mineral not containing the target element. H2 is the distribution rate when the edge of the target mineral has cracks, at least one other mineral containing the target element, and other minerals that do not contain the target element but exclude metal sulfides. H3 is the distribution rate when the target mineral's edge simultaneously contains metal sulfides, at least one other mineral containing the target element, and a mineral that does not contain the target element; H4 is the distribution rate when at least one other mineral containing the target element and a mineral without the target element are present at the edge of the target mineral; H5 is the distribution rate when the edge of the target mineral is entirely composed of metal sulfides and is in intergranular contact. H6 is the distribution rate when the edge of the target mineral is entirely composed of other minerals containing the target element and is in intergranular contact. H7 is the distribution rate when the edge of the target mineral is entirely composed of other minerals that do not contain the target element and are in intergranular contact. H8 represents the distribution rate when the entire edge of the target mineral is the same type of mineral and is in contact with the surrounding mineral.

[0009] As a further improvement of the present invention, in step S2, the calculation formula for the interparticle correction coefficient is as follows: c = Sa / (Sa+Sb); In the formula, c is the intergranular correction coefficient, Sa is the sum of the areas of target minerals enclosed by non-target minerals and containing cracks in the enclosed areas, and Sb is the sum of the areas of target minerals enclosed by non-target minerals and not containing cracks in the enclosed areas.

[0010] As a further improvement of the present invention, in step S4, the formula for calculating the centroid distance dn.m is as follows: dn.m = 0.5 ×(dn.m max +dn.m min ); In the formula, dn.m max Let dn.m be the longest distance from the centroid of the nth target mineral grain to any point on the contact boundary of the mth non-target mineral or pore. min It is the shortest distance from the centroid of the nth type of target mineral grain to any point on the contact boundary of the mth type of non-target mineral or pore; Non-target mineral category m includes at least one of the following classifications: m=1 represents other metal sulfides that do not contain the target element; m=2, representing other minerals containing the target element; m=3 represents minerals other than m=1 and m=2, which are minerals that do not contain the target element; m=4, representing porosity.

[0011] As a further improvement of the present invention, in step S5, the formula for calculating the effective area Rn.m is as follows: Rn.m = 0.5 × dn.m × Ln.m; In the formula, dn.m is the average distance from the centroid of the nth target mineral particle to the boundary of the mth mineral or pore contact; Ln.m is the sum of the side lengths of the mth non-target mineral or the nth target mineral particle in pore contact; The formula for calculating the effective area weight q is as follows: q = Rn.m / ΣRn.m; In the formula, ΣRn.m is the sum of the effective areas of the contact regions between the same target mineral particles and all types of non-target minerals.

[0012] As a further improvement of the present invention, in step S3, the formula for calculating the relative content percentage Wn.e of the target mineral particles is as follows: Wn.e = Sn.e / ΣSn.e; In the formula, Sn is the particle area of ​​the nth target mineral particle; Sn.e is the area of ​​the nth target mineral particle on the eth measurement surface of the sample to be tested.

[0013] As a further improvement of the present invention, the pore is defined as a region where mineral particles do not directly contact each other and the gap is greater than or equal to 5 μm; the crack is defined as a region where mineral particles directly contact each other and the gap is less than 5 μm.

[0014] As a further improvement of the present invention, in step S1, the preparation of the three-dimensional multiface includes: cutting the sample to be tested into f cubes of similar size, f≥6, with a side length difference ≤5%; taking any three adjacent planes of each cube as the test face, wherein the three planes intersect at a common vertex.

[0015] As a further improvement of the present invention, in step S2, in the intergranular contact identification step, a dye is used to stain the polished test surface, and then the encapsulation state with and without cracks is distinguished by microscopic observation; the dye is selected from at least one of red oil, kerosene, fluorescent agent, and PFINDER 860; the number of target mineral edge particles is measured to be ≥200 during microscopic observation.

[0016] Beneficial effects: 1. The method provided by this invention systematically quantifies the embedding state of the target mineral. By distinguishing between "intergranular contact" (including cracks) and "encapsulated contact" (without cracks), and introducing an intergranular correction coefficient c, it can more accurately determine whether the target mineral is at the mineral particle boundary or is completely encapsulated, providing a key basis for subsequent mineral processing (such as grinding and liberation).

[0017] 2. The method provided by this invention uses multi-faceted measurement to significantly enhance representativeness. It independently analyzes the three adjacent faces (sharing a vertex) of the sample, which significantly improves the statistical representativeness, avoids the directional bias caused by single-plane measurement, and more realistically reflects the embedding relationship of minerals in three-dimensional space.

[0018] 3. The method provided by this invention achieves a refined description of contact characteristics. By measuring the centroid distance and contact edge length of the target mineral and calculating the effective area weight, it realizes a quantitative evaluation of the contact intensity between mineral particles and different non-target minerals (including pores) around them.

[0019] 4. The method provided by this invention constructs clearly categorized embedding state parameters, which include multiple feature parameters (H1~H8) capable of distinguishing the types of minerals in edge contact (metal sulfides, other minerals containing the target element, other minerals, pores); the contact range level (four-level intervals); and whether it is a single, completely encapsulated state. This allows for digital comparison of the embedding characteristics of different samples or different mining areas.

[0020] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and in order to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Attached Figure Description

[0021] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the present invention will be briefly described below. Obviously, the drawings described below are merely some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0022] Figure 1 This is a flowchart illustrating the method for analyzing the non-encapsulated mineral embedding state provided in this embodiment of the invention. Detailed Implementation

[0023] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. These embodiments are merely illustrative of the technical solution of the present invention and are therefore intended to limit the scope of protection of the present invention.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the invention, are intended to cover non-exclusive inclusion.

[0025] In the description of the embodiments of this invention, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this invention, "multiple" means two or more, unless otherwise explicitly defined.

[0026] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0027] In the description of the embodiments of this invention, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0028] In the description of the embodiments of the present invention, the term "multiple" refers to two or more (including two), similarly, "multiple groups" refers to two or more (including two groups), and "multiple pieces" refers to two or more (including two pieces).

[0029] In the description of the embodiments of the present invention, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of the present invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of the present invention.

[0030] To address the technical problem that existing technologies cannot systematically and quantitatively characterize the intergranular contact, porosity distribution, and crystallization ratio of non-enclosed minerals, leading to large prediction errors in liberation degree and hindering guidance for mineral processing design, this invention provides an analytical method for the embedding state of non-enclosed minerals. First, a method for distinguishing between intergranular and enclosed states based on fracture identification is constructed. Through staining microscopy, the contact boundary between the target mineral and surrounding minerals is divided into two categories: fracture-containing (intergranular contact) and fracture-free (enclosed contact), and an intergranular correction coefficient c is calculated. Fractures represent natural weak surfaces between particles and are preferential channels for grinding liberation; the c value quantitatively characterizes the proportion of the target mineral at the particle boundary, providing a core correction coefficient for subsequent differentiation between easily liberated (non-enclosed) and difficult-to-liberate (enclosed) states. Then, a contact intensity quantification method based on centroid distance and contact edge length is employed. The average distance from the centroid of the target mineral particle to the contact edge and the contact edge length are measured to construct the effective area of ​​the contact region, which is then normalized to obtain the effective area weight. This value reflects the actual control degree of each non-target mineral (or pore) in the particle interface, transforming the abstract embedding relationship into a comparable contact strength index. Finally, a comprehensive modeling method combining multi-faceted weighted statistics and hierarchical inversion is constructed. Measurements are taken on the three adjacent faces of each sample, and particle area weights obtained from automated mineralogical analysis (avoiding particle number bias) are used to accumulate and average the values ​​according to the type of contact mineral and the proportion of contact area, yielding characteristic parameters. Simultaneously, the proportion of fully enclosed states is inverted using the intergranular correction coefficient c and the proportion of single-mineral contact between pure grains. This achieves accurate extrapolation from two-dimensional cross-sections to three-dimensional volume equivalents. The system outputs quantitative results of the internal differences in non-enclosed states (intergranular, porosity, different degrees of crystallization) and the proportion of enclosed states.

[0031] Please refer to Figure 1 As shown, this embodiment of the invention provides a method for analyzing the non-encapsulated mineral embedding state, including the following steps: S1, Sample Preparation Take the block sample to be tested and cut it into 6 or more cubes of similar size (f blocks), with a side length difference of less than or equal to 5%. For each cut sample, take any three adjacent planes as a group of test surfaces (the three test surfaces are in contact with a common vertex; measuring three surfaces increases the representativeness of the sample measurement data in a three-dimensional manner). Grind the test surfaces of the sample (the final effect is a smooth but rough surface – to increase the adhesion of the resin adhesive). Apply resin to this surface and remove air bubbles by vacuuming. The purpose is to fill the internal pores of the sample with the resin adhesive mixture, reducing errors for further pore analysis. Then, perform polishing.

[0032] S2, Microscopic analysis (interparticle contact identification) The test surfaces from step S1 are uniformly stained, and then polished with a cloth (or with 0.5 micrometers of abrasive added) for 5-10 minutes. The samples from step S1 are tested and analyzed under a microscope. The sum of the areas of the target minerals encased by non-target minerals (including cracks, representing intergranular contact) and the target minerals encased by non-target minerals (excluding cracks, representing non-intergranular contact) are randomly measured and denoted as Sa and Sb, respectively. The intergranular correction coefficient c = Sa / (Sa+Sb) represents the proportion of the target mineral located between mineral grains.

[0033] Preferred staining reagents include red oil, kerosene, fluorescent agents, and PFINDER 860. The staining procedure is as follows: Dip a glass rod into the stain and apply it evenly to the measurement surface, allowing it to stand for 3-5 minutes.

[0034] The non-target minerals are preferably other metal sulfides (excluding the main recovered elements in the target mineral; for example, copper is the target element in chalcopyrite, while pyrite does not contain copper and is therefore a metal sulfide excluding the target element), other minerals containing the target element (chalcocite contains copper and is therefore another mineral containing the target element, including the main recovered copper element in the target mineral), and other minerals.

[0035] During microscopic analysis, the number of particles at the edge of the target mineral is greater than or equal to 200.

[0036] Among them, cracks refer to direct contact between mineral particles with gaps of less than 5μm.

[0037] S3, Automated Mineralogical Analysis (Particle Information Acquisition) Carbon is sprayed onto the surface to be measured of the sample after step S2, with a carbon spraying depth of 10~20 nm.

[0038] Automated mineralogical analysis is performed on the sample surface to be tested after carbon spraying to obtain the particle area Sn of the target mineral particles (n is the number of the target mineral particles); then the relative content percentage of the target mineral particles is Wn.e, Wn.e=Sn.e / ΣSn.e, where Sn.e is the area of ​​the nth target mineral particle on a certain measurement surface of a certain sample.

[0039] ΣSn.e calculates the sum of particle areas on only one face; e represents the three measurement faces of a sample, which are 1, 2, and 3 respectively.

[0040] S4, Measurement of Geometric Parameters of Target Mineral S41, Measure the centroid distance dn.m of the target mineral particles (m is the type of non-target mineral particles in contact), dn.m = 0.5 × (dn.m max +dn.m min ), dn.m maxLet dn.m be the longest distance from the centroid of the nth mineral grain to any point on the contact edge of the mth mineral or pore. min It represents the shortest distance from the centroid of the nth type of mineral grain to any point on the contact edge of the mth type of mineral or pore.

[0041] S42, measure the contact edge length Ln.m of the target mineral particles, which represents the sum of the edge lengths of the nth target mineral particles in contact with the mth non-target mineral or pore; m is 1, 2, 3, 4, representing other metal sulfides (excluding the target element), other minerals containing the target element, other minerals (excluding the target element), and pores, respectively.

[0042] Porosity refers to the gap between mineral particles that are not in direct contact and are greater than or equal to 5 μm.

[0043] S5, Calculation of contact characteristic parameters Effective area weight q = Rn.m / ΣRn.m; The effective area of ​​the contact region is Rn.m, where Rn.m = 0.5 × dn.m × Ln.m; ΣRn.m only calculates the data for the nth single particle.

[0044] S6, Calculation of the embedding state of the target mineral The specific parameters for calculating the embedding state of the target mineral are as follows: S61, Hp.q=1 / 3×ΣWn.e / f, p is 1~4, q is the effective area weight, Q is the contact range interval, and the contact range interval Q is divided into zone 1, zone 2, zone 3 and zone 4 according to the proportion of the effective area weight q, which respectively represent greater than 0% and less than or equal to 25%, greater than 25% and less than or equal to 50%, greater than 50% and less than or equal to 75%, and greater than 75% and less than or equal to 100%.

[0045] The effective area weight q = Rn.m / ΣRn.m is used to calculate the weight value of an individual particle. Different types of particles are classified based on these weight values, and then these particles are grouped and calculated accordingly. However, machine measurements cannot distinguish between fractured particles; an interparticle correction factor c is needed to calculate the proportion of particles containing fractures (interparticles).

[0046] H1 represents the distribution rate of the target mineral when its edges are fissures and metal sulfides, and it may contain other minerals containing the target element, or one or two other minerals (excluding the target element). H2 represents the distribution rate of other minerals containing the target element, or one or two other minerals (excluding the target element), when the edge of the target mineral is a fracture. H3 represents the distribution rate of the target mineral when its edge is a metal sulfide, and it may contain other minerals containing the target element, or one or two other minerals (excluding the target element). H4 represents the distribution rate when the target mineral is surrounded by other minerals containing the target element, or one or two other minerals (excluding the target element).

[0047] S62, Hp=1 / 3×ΣWn.e / f, p is 5~7.

[0048] H5 refers to the target mineral whose edges are entirely composed of metal sulfide particles, and which are located between the particles; H6 is when the edge of the target mineral is entirely composed of other mineral particles containing the target element, and these particles are located between the particles; H7 represents the target mineral whose edges are entirely composed of other mineral particles (excluding the target element) and which are located between the particles.

[0049] S63, H8=(1-c)×(H5+H6+H7) / c.

[0050] Among them, H8 is when the edge of the target mineral is entirely composed of the same mineral, that is, in an encapsulated state, not between particles.

[0051] p represents the contact type, and Q represents the contact range. For specific values ​​and classifications, please refer to Table 1.

[0052] Table 1. Measurement results of the embedding state of the target mineral. Example 1 Embodiment 1 of the present invention provides an analytical method for the non-encapsulated chalcopyrite embedding state in a polymetallic ore, comprising the following steps: S1, Sample Preparation: Take the block sample to be tested (minimum particle size greater than or equal to 3.0 cm), cut the sample into 10 cubes of similar size (particle size 1.50~2.50 cm), with a side length difference of less than 5%. Take any three adjacent planes of each cut sample as the test surface (the three test surfaces share a common vertex). Grind the test surface of the sample (preferably using 200-mesh abrasive for 5~10 min, the final effect is a smooth surface). Apply adhesive to this surface (epoxy resin and its corresponding curing agent at a volume ratio of 1.0:(0.2~1.0), the resin layer height is controlled at 1.0~1.5 cm), remove air bubbles by vacuuming, and then place it in a constant temperature environment of 45~65℃ to accelerate curing.

[0053] Then, grinding and polishing are carried out using 800 mesh, 120 mesh, 6μm, 3μm and 0.5μm abrasives.

[0054] S2, Microscopic Analysis: The test surface from step S1 was uniformly stained with red oil, and then polished with a velvet cloth (0.5μm abrasive). The sample from step S1 was tested and analyzed under a microscope. The sum of the areas of the target mineral encased by non-target minerals (including fractures, representing intergranular contact) and the target mineral encased by non-target minerals (excluding fractures, representing non-intergranular contact) were randomly measured and denoted as Sa and Sb, respectively.

[0055] The interparticle correction coefficient c = Sa / (Sa + Sb) = 1.80 × 10 4 / (1.80×10 4 +7.36×10 3 =0.71, see Table 2 for details.

[0056] Table 2. Results of Microscopic Analysis S3. Spray 10 nm of carbon onto the surface to be measured of the sample after S2 test. Perform automatic mineralogical analysis on the surface to be measured of the sample after carbon spraying to obtain the particle area Sn.e of the target mineral particles (n is the number of the target mineral particles). Then the relative content percentage of the target mineral particles is Wn.e, Wn.e=Sn.e / ΣSn.e, see Table 3 for details.

[0057] Table 3 Results of Automatic Mineralogical Analysis of Chalcopyrite (Partial Data from Block 1 and Block 10) S4, Measurement of Geometric Parameters of Target Mineral S41, Measure the centroid distance dn.m of the target mineral particles (m is the type of non-target mineral particles in contact), where dn.m = 0.5 × (dn.m max +dn.m min ), dn.m max Let dn.m be the longest distance from the centroid to any point on the contact edge (the m-th mineral). min It is the shortest distance from the centroid to any point on the contact edge (the m-th mineral).

[0058] S42, measure the contact edge length Ln.m of the target mineral particles, which represents the sum of the edge lengths of the m-th non-target mineral in contact with the target mineral, as shown in Table 4.

[0059] Table 4. Geometric Parameter Measurement Results (First Part of the Data) S5, Calculation of contact characteristic parameters The effective area weight q = Rn.m / ΣRn.m, where the effective area of ​​the contact region is Rn.m, Rn.m = 0.5 × dn.m × Ln.m, as detailed in Tables 5-1 and 5-2.

[0060] Table 5-1 Calculation Results of Contact Characteristic Parameters (First Part of the Data) Table 5-2 Calculation Results of Contact Characteristic Parameters (Part Ten Data) S6, Calculation of the embedding state of the target mineral See Table 6 for details.

[0061] Table 6 Measurement Results of Copper Ore Found State Example calculations are as follows: H1.2=1 / 3×(23.38+164.15+……+99.94)×10 -5 / 10=5.24%; H5=1 / 3×(8.37+164.15+……+304.35)×10 -5 / 10×0.71=6.42%; H8=(1-c)×(H5+H6+H7) / c=(1-0.71)×(6.42%+2.46%+10.32%) / 0.71=7.84%.

[0062] Interpretation and analysis of results: 1. The target mineral is mainly in the intergranular / pore state. When the corresponding Hp.q value is high, the target mineral is easily liberated.

[0063] 2. When the target mineral is highly intergrowthed with a certain type of mineral, and the corresponding Hp.q value is high, fine grinding or specific reagents are required.

[0064] In summary, this invention discloses an analytical method for the embedding state of unencapsulated minerals, belonging to the technical fields of geological testing and analysis and process mineralogy. The steps include: preparing multifaceted block samples and applying a gel; distinguishing between fractured and non-fractured mineral contacts under a microscope and calculating intergranular correction coefficients; obtaining the area weight of the target mineral particles through automated mineralogical analysis; measuring the centroid distance and contact edge length of the mineral particles and calculating the effective area weight; and finally constructing multiple embedding state characteristic parameters (H1~H8) to quantify the intergranular contact state, porosity contact state, and the proportion of intergranular crystals, as well as the contact range level, of the target mineral. This invention can systematically distinguish between unencapsulated and encapsulated minerals, refine the characterization of intergranular crystal proportions and contact intensity, significantly improve the accuracy of dissociation behavior prediction, and provide reliable and comparable quantitative basis for mineral processing design.

[0065] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments that have the same structure and perform the same effects as the technical concept within the scope of the present invention are included within the scope of the present invention. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of the present invention, are also included within the scope of the present invention.

Claims

1. A method for analyzing the non-encapsulated mineral embedding state, characterized in that, The steps include the following: S1, Sample processing: Prepare three-dimensional multi-faceted samples to obtain at least three adjacent test surfaces that share a vertex; S2, Intergranular contact identification: Optical microscopy analysis is performed on the surface to be tested to obtain the contact type parameters of the target mineral in the ore. The contact type parameters include an intergranular correction coefficient used to characterize the proportion of the target mineral in the intergranular contact state. S3, Particle Information Acquisition: Perform automatic mineralogical analysis on the surface to be measured to obtain the area parameters of the target mineral particles; S4, Contact geometry measurement: Measure the geometric contact parameters of the target mineral particles, including the centroid distance of the target mineral particles and the contact edge length of the target mineral particles; S5, Calculation of contact characteristic parameters: Calculate the contact characteristic parameters for each contact type based on the contact side length and the centroid distance; the contact characteristic parameters include the effective area of ​​the contact region between the target mineral particle and the non-target mineral, and the weight of the effective area relative to the total effective area of ​​all contact regions of the target mineral particle; S6, quantitative embedding state: Based on the contact characteristic parameters and combined with the intergranular correction coefficient and area parameters, calculate the embedding state characteristic parameters of the target mineral to quantitatively characterize the intergranular contact, pore contact and crystallization ratio of the target mineral.

2. The method for analyzing the non-encapsulated mineral embedding state according to claim 1, characterized in that, In step S6, the embedding state characteristic parameters include H1~H8 classified according to the type of contact mineral and the contact range interval. H1~H4 are classified according to the effective area weight of the contact range interval to characterize the embedding distribution rate of different mineral combinations and cracks / pores. H5~H7 characterize the embedding distribution rate of the target mineral edge being a single mineral and located between grains. H8 characterizes the encapsulation state distribution rate of the target mineral edge being the same type of mineral. The distribution rate of the target mineral's embedding state is calculated using the following formula: Hp.q = (1 / 3) × ΣWn.e / f, where p is 1~4, q is the effective area weight, Q is the contact range, Wn.e is the relative percentage of the target mineral particles, n is the number of the target mineral particles, f is the number of sample blocks, and e is the face number of the sample measurement surface; or Hp = (1 / 3) × ΣWn.e / f, where p is 5~7; or H8 = (1-c) × (H5+H6+H7) / c; where c is the interparticle correction coefficient; The contact range interval Q is divided into the following categories according to the proportion of effective area weight q: greater than 0% and less than or equal to 25%, greater than 25% and less than or equal to 50%, greater than 50% and less than or equal to 75%, and greater than 75% and less than or equal to 100%.

3. The analytical method for the non-encapsulated mineral embedding state according to claim 2, characterized in that, The distribution rate of the embedded state includes the following parameters: H1 is the distribution rate when the edge of the target mineral simultaneously contains fissures, metal sulfides, and at least one other mineral containing the target element and another other mineral not containing the target element. H2 is the distribution rate when the edge of the target mineral has cracks, at least one other mineral containing the target element, and other minerals that do not contain the target element but exclude metal sulfides. H3 is the distribution rate when the target mineral's edge simultaneously contains metal sulfides, at least one other mineral containing the target element, and a mineral that does not contain the target element; H4 is the distribution rate when at least one other mineral containing the target element and a mineral without the target element are present at the edge of the target mineral; H5 is the distribution rate when the edge of the target mineral is entirely composed of metal sulfides and is in intergranular contact. H6 is the distribution rate when the edge of the target mineral is entirely composed of other minerals containing the target element and is in intergranular contact. H7 is the distribution rate when the edge of the target mineral is entirely composed of other minerals that do not contain the target element and are in intergranular contact. H8 represents the distribution rate when the entire edge of the target mineral is the same type of mineral and is in contact with the surrounding mineral.

4. The method for analyzing the non-encapsulated mineral embedding state according to claim 2, characterized in that, In step S2, the formula for calculating the interparticle correction coefficient is as follows: c = Sa / (Sa+Sb); In the formula, c is the intergranular correction coefficient, Sa is the sum of the areas of target minerals enclosed by non-target minerals and containing cracks in the enclosed areas, and Sb is the sum of the areas of target minerals enclosed by non-target minerals and not containing cracks in the enclosed areas.

5. The method for analyzing the non-encapsulated mineral embedding state according to claim 3, characterized in that, In step S4, the formula for calculating the centroid distance dn.m is as follows: dn.m = 0.5 ×(dn.m max +dn.m min ); In the formula, dn.m max Let dn.m be the longest distance from the centroid of the nth target mineral grain to any point on the contact boundary of the mth non-target mineral or pore. min It is the shortest distance from the centroid of the nth type of target mineral grain to any point on the contact boundary of the mth type of non-target mineral or pore; m represents a non-target mineral category, including at least one of the following classifications: m=1, characterizing metal sulfides that do not contain the target element; m=2, representing other minerals containing the target element; m=3 represents minerals other than m=1 and m=2, which are minerals that do not contain the target element; m=4, representing porosity.

6. The method for analyzing the non-encapsulated mineral embedding state according to claim 5, characterized in that, In step S5, the formula for calculating the effective area Rn.m is as follows: Rn.m = 0.5 × dn.m × Ln.m; In the formula, dn.m is the average distance from the centroid of the nth type of target mineral grain to the contact boundary of the mth type of mineral or pore; Ln.m is the sum of the side lengths of the m-th non-target mineral or the n-th target mineral particles in pore contact; The formula for calculating the effective area weight q is as follows: q = Rn.m / ΣRn.m; In the formula, ΣRn.m is the sum of the effective areas of the contact regions between the same target mineral particles and all types of non-target minerals.

7. The analytical method for the non-encapsulated mineral embedding state according to claim 2, characterized in that, In step S3, the formula for calculating the relative content percentage Wn.e of the target mineral particles is as follows: Wn.e = Sn.e / ΣSn.e; In the formula, Sn is the particle area of ​​the nth target mineral particle in the sample to be tested; Sn.e is the area of ​​the nth target mineral particle on the eth measurement surface of the sample to be tested.

8. The analytical method for the non-encapsulated mineral embedding state according to claim 2, characterized in that, The pores are defined as regions where mineral particles do not directly contact each other and the gaps are greater than or equal to 5 μm; the cracks are defined as regions where mineral particles directly contact each other and the gaps are less than 5 μm.

9. The method for analyzing the non-encapsulated mineral embedding state according to claim 2, characterized in that, In step S1, the preparation of the three-dimensional multiface includes: cutting the sample to be tested into f cubes of similar size, f≥6, with a side length difference ≤5%; taking any three adjacent planes of each cube as the test face, and the three planes intersect at a common vertex.

10. The method for analyzing the non-encapsulated mineral embedding state according to claim 1, characterized in that, In step S2, the intergranular contact identification step involves using a dye to stain the polished surface to be tested, and then observing it under a microscope to distinguish between the encapsulation state with and without cracks. The dye is selected from at least one of red oil, kerosene, fluorescent agent, and PFINDER860. During the microscope observation, the number of particles on the edge of the target mineral is measured to be ≥200.

Citation Information

Patent Citations

  • Method for measuring three-dimensional form of gold mineral

    CN119164737A

  • Method for measuring structural coefficient

    CN120314555A